Thiol/Disulfide System Plays a Crucial Role in Redox Protection in the Acidophilic Iron-Oxidizing Bacterium Leptospirillum Ferriphilum - Levican-Jaque, G; Chavez-Rosales, R (2012)
Thiol/disulfide systems are involved in the maintenance of the redox status of proteins and other molecules that contain thiol/disulfide groups. Leptospirillum ferriphilum DSM14647, an acidophilic bacterium that uses Fe2+ as electron donor, and withstands very high concentrations of iron and other redox active metals, is a good model to study how acidophiles preserve the thiol/disulfide balance. We studied the composition of thiol/disulfide systems and their role in the oxidative stress response in this extremophile bacterium. Bioinformatic analysis using genomic data and enzymatic assays using protein extracts from cells grown under oxidative stress revealed that the major thiol/disulfide system from L. ferriphilum are a cytoplasmic thioredoxin system (composed by thioredoxins Trx and thioredoxin reductase TR), periplasmic thiol oxidation system (DsbA/DsbB) and a c-type cytochrome maturation system (DsbD/DsbE). Upon exposure of L. ferriphilum to reactive oxygen species (ROS)-generating compounds, transcriptional activation of the genes encoding Trxs and the TR enzyme, which results in an increase of the corresponding activity, was observed. Altogether these data suggest that the thioredoxin-based thiol/disulfide system plays an important role in redox protection of L. ferriphilum favoring the survival of this microorganism under extreme environmental oxidative conditions. © 2012 Norambuena et al.